The faces of muslim/christian peaceful coexistence and shariah application in Nigeria (2015)
This paper focuses on the complexity of peaceful coexistence between Muslims and Christians in Nigeria and how this affects their understanding of the place of the Shari' ah in modern Nigeria. This paper questions the popular reading of the origin and development of the Shari'ah imbroglio in Nigeria and locates this in the desires of both Muslims and Christians to claim their portions of the "national cake" or the nation's resources. Though the paper agrees that there are indeed elements of what can be termed 'political Islam and Christianity' in Muslim/Christian relations in Nigeria, it explains how the prevailing Boko Haram quagmire can be traced to the dangerous play with politics in Nigerian recent history. It finally shows how this menace can be curbed through the application of some principles that intersect with Muslim/non-Muslim peaceful coexistence, pluralism and religious dialogue as being realized in Malaysia today. It also explains how this Malaysian example can help in re-directing the future relations of Muslims and Christians in Nigeria towards a sustainable, peaceful, multicultural, religious and equitable Nigerian society.